Energy policy analysis with the Boğaziçi University energy modeling system BUEMS: prospects for the diffusion of renewable energy tecnologies and utilization of domestic coal reserves in Turkey - Yıldırım, Fazlı İlke. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this thesis, the relationship among the use of renewable energy technologies, the use of coal resources and the implied changes in CO2 emission between 2017 and 2047 in Turkey are examined. This thesis aims to reveal cost and emission implications under various renewable energy and coal policy scenarios and guide government and private sector policy-makers to make more eﬃcient and cost-eﬀective investments. In this study, puclicly available data of the Turkish Electricity Transmission Cor poration (TEIAS), the Turkish Statistical Institute (TUIK), the Ministry of Energy and Natural Resources, the World Energy Council Turkish National Committee are used to estimate the useful energy demand as exogenous input into the Bog˘azi¸ci University Energy Modeling System (BUEMS). The base scenario results indicate 82% growth in total energy-related CO2 emis sions between 2017 - 2047. A 15% reduction in total CO2 emission is projected in 2047, if the electricity generation targets for wind and solar power technologies set in Renew able Energy Resource Zone (YEKA) tenders are reached. It is observed that, direct emission scenarios are more cost-eﬀective in decreasing CO2 emission what compared to taxation and decreases total CO2 emission more than sectoral emission scenarios in the long term.
Keywords: Renewable energy sources -- Turkey.